Serum lipid profile in HCV patients treated with direct-acting antivirals: a systematic review and meta-analysis - Villani, Rosanna (Sci Rep, 2021)
Although direct-acting antivirals are very effective and safe drugs, several authors have reported the alteration of lipid profile during and after anti-HCV therapy suggesting a potential impact on the risk of cardiovascular events. We performed a systematic review and meta-analysis of observational studies to investigate the magnitude and temporal trend of lipid profile changes in DAA treated patients. All selected studies included data on lipid profile before starting therapy and at least one follow-up assessment during or after antiviral treatment. We identified 14 studies (N = 1537 patients) after removing duplicates. Pooled data showed an increase in total cholesterol 4 weeks after starting therapy (+ 15.86 mg/dl; 95% CI + 9.68 to 22.05; p < 0.001) and 12 weeks after treatment completion (+ 17.05 mg/dl; 95% CI + 11.24 to 22.85; p < 0.001). LDL trend was similar to the total cholesterol change in overall analysis. A mean increase in HDL-cholesterol of 3.36 mg/dl (95% CI + 0.92 to 5.79; p = 0.07) was observed after 12 weeks of treatment, whereas at SVR24 HDL difference was + 4.34 mg/dl (95% CI + 1.40 to 7.28; p = 0.004).Triglycerides did not show significant changes during treatment and after treatment completion. DAAs induce mild lipid changes in chronic hepatitis C patients treated with DAAs, which may persist after treatment completion.